Public Governance of Value-Based Public Policy: Indonesia’s Halal Certification in a Global Regulatory Context - Abdul Razak Nasution; Mohsen Bahmani (CV. RADJA PUBLIKA, 2026)
How can states design and implement value-based public policies while honoring multilateral trade commitments? Indonesia’s mandatory halal certification regime provides a revealing case. This article examines the policy-making challenges involved in designing certification requirements that reflect societal values and public morals while maintaining consistency with World Trade Organization (WTO) disciplines. The analysis explores how the Agreement on Technical Barriers to Trade (TBT) and GATT Article XX(a) shape the policy space available for value-based public policies affecting international trade. Evidence from WTO TBT notifications and Specific Trade Concerns (STC ID 502) indicates persistent tensions related to non-discrimination, necessity, and transparency. These tensions, however, do not necessarily result in zero-sum outcomes. Through proportionate policy design, risk-based implementation, and strategic international cooperation, domestic policy objectives can be pursued alongside international regulatory consistency. The article develops a governance framework encompassing tiered recognition mechanisms, enhanced transparency, technological innovation, and cooperative standards development. The findings contribute to debates on public governance by illustrating how international regulatory frameworks constrain, yet do not eliminate, national policy autonomy.